Sistem Pakar Berbasis Web untuk Pengenalan Dini terhadap Karakter Investasi Individu - Sano, Albert V. Dian (ComTech: Computer, Mathematics and Engineering Applications, 2012)
The objective of this research is to develop a web-based expert system for early detection towards characters of investment of people who will invest immediately on their productive ages. The development of this application is encompassing four primary activities in developing an expert system, namely: knowledgeacquisition, knowledge representation, knowledge inferencing, and knowledge transfering. Knowledge acquisition is a process of acquisition or transfering knowledge or expertise of an expert through a knowledge engineer. Knowledge representation is a process of transfering knowledge into a computer based system. Knowledge inferencing is a reasoning process performed by an expert system to draw a conclusion or a final result. The reasoning process applies a forward-chaining method. Knowledge transfering is a process of transfering knowledge from an expert system to a user (non-expert one) through a user interface of the expert system. This expert system has been tested to about 300 users. This simple system generally runs quite well although there are still some weakness to refine in the further research.